Studi Tinjauan Perencanaan Sistem Plumbing Air Bersih (Studi Kasus: Gedung Sekolah Tinggi Ilmu Bahasa Arab) - Sugiarto Badaruddin (Politeknik Negeri Ujung Pandang, 2023)
carefully considered to ensure that the water demand of the students and staff can be met effectively and efficiently. Calculations show that a water demand of 0.35 m3/min is required, and various existing pipe diameters are used, ranging from 65mm for the main pipes, 60mm and 50mm for the header pipes, to 40mm, 32mm, 30mm, 25mm, 20mm, and 15mm for the shaft pipes. However, after controlling for velocity values using Epanet software, it was found that some pipes had values below 1.8m/s and above 2.4m/s, which could compromise system efficiency. Therefore, the effective pipe diameter for the header pipes was found to be 125mm and 90mm, and for the shaft pipes, it ranged from 90mm to 15mm. The results of this study highlight that the clean water piping system in the STIBA building must be carefully designed and evaluated to meet the clean water demands of the students and staff effectively and efficiently. This can be achieved by selecting effective pipe diameters based on the Epanet calculations and ensuring that the velocity values remain within the specified limits.